Moderation of Locus of Control in the Development of Android-Based Google Site Interactive Learning Media to Improve Learning Outcomes - Syahputra, Edy; Hutasuhut, Saidun; Hasyim (Universitas Veteran Bangun Nusantara, 2024)
This article is based on the lack of learning outcomes, internal control, and the use of interactive media. The purpose of this study is to understand the worthiness and effectiveness of the Android-based Google Site interactive learning media, as well as the interaction of locus of control with the Android-based Google Site interactive learning media on student learning outcomes. This thesis is a development using the Four-D model. The information collection instrument uses expert validation questionnaires, teacher, and student feedback. The research population was class XI students. The results reveal that the interactive learning media Google Site based on Android is worth using. based on the validation of material experts at 46.20 in the very valid group, media experts at 4.60 in the very valid group, teaching material design experts at 4.63 in the very feasible category, and learning design experts at 4.72 in the very feasible category. The economics teacher's assessment was 4.76 in the very decent category, the results of the individual trial were 4.67 in the very decent category, the small group test was 4.79 in the very decent category, and the field trial was 4.72 in the very decent category. The Android-based Google Site interactive teaching media is effectively used in improving learning outcomes in line with the t-test results, where the 2-tailed sig value is 0.000<0.05. Based on the two-way ANOVA test, there is no locus of control interaction on the Google Site interactive learning media, namely the 2-tailed sig value is 0.001<0.05. In conclusion, there is an interaction between locus of control and learning media on student learning outcomes. This research implies that schools can use the Android-based interactive learning media Google Site